A methodology to quantitatively evaluate the safety of a glazing robot - Lee, Seungyeol; Yu, Seungnam; Choi, Junho; Han, Changsoo (ELSEVIER SCI LTD, 2011)
A new construction method using robots is spreading widely among construction sites in order to overcome labour shortages and frequent construction accidents. Along with economical efficiency, safety is a very important factor for evaluating the use of construction robots in construction sites. However, the quantitative evaluation of safety is difficult compared with that of economical efficiency. In this study, we suggested a safety evaluation methodology by defining the 'worker' and 'work conditions' as two risk factors, defining the 'worker' factor as posture load and the 'work conditions' factor as the work environment and the risk exposure time. The posture load evaluation reflects the risk of musculoskeletal disorders which can be caused by work posture and the risk of accidents which can be caused by reduced concentration. We evaluated the risk factors that may cause various accidents such as falling, colliding, capsizing, and squeezing in work environments, and evaluated the operational risk by considering worker exposure time to risky work environments. With the results of the evaluations for each factor, we calculated the general operational risk and deduced the improvement ratio in operational safety by introducing a construction robot. To verify these results, we compared the safety of the existing human manual labour and the proposed robotic labour construction methods for manipulating large glass panels. (C) 2010 Elsevier Ltd and The Ergonomics Society. All rights reserved.
Keywords: CONSTRUCTION; DESIGN